Software for information storage and retrieval tested, evaluated and compared: general introduction... part 1. - Sieverts EG; Hofstede M (Electronic Library, 1991)
In this first article of a series, several categories of microcomputer software for information storage and retrieval are distinguished and characterised: (1) classical retrieval systems, (2) end-user software, (3) indexing programs, (4) full-text retrieval programs, and (5) personal information managers. In addition, the special retrieval techniques of hypertext and best-match searching are discussed. The 20-odd programs which will be assessed in subsequent articles are characterised according to these categories. As an introduction to the coming comparison and assessment, a systematic listing and discussion of properties and functions of ISR software is presented.